Deep drawing with unconventional tooling: impact of process parameters on a part accuracy - Ilić, Jovica; Grbić, Tatjana; Hadžistević, Miodrag; Milutinović, Mladomir; Kraišnik, Milija; Movrin, Dejan (Advanced Technologies and Materials, 2023)
The analysis of influencing factors and their effects on the deep drawing process is essential for producing cost-effective, high-quality workpieces. In this study, the impact of deep drawing process variables, including die radius, blank holder force, and lubrication conditions, on the distribution of wall thickness and changes in radius for axisymmetric workpieces is explored. For the investigation, specialized tooling was created, with core components such as the punch, die, and blank holder made from a two-component resin and fabricated using rapid tooling technology - vacuum casting. The Taguchi method was employed as a statistical tool for planning the experiments, which allowed the impact of process factors to be determined with minimal variability.